2018
DOI: 10.22610/jebs.v10i2(j).2217
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Effect of Work-Life Balance on Job Satisfaction

Abstract: In emerging cultures, job satisfaction and work-life balance are ongoing factors in gaining the ultimate competitive advantage for organizations. Work-life balance is a core ingredient for job satisfaction and for quality work performance, and employees need to have a sense of commitment to their jobs. The study attempts to determinethe extent to which work-life balance has a moderating effect onjob satisfaction in a call centre organization. The approach for the study was quantitative, and a self-developed qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Extant research on WLB focused on the antecedent conditions (Alegre and Pasamar, 2018;Delanoeije et al, 2019;Gounder and Govender, 2018;Nizam and Kam, 2018), but the research focusing on the consequences of WLB is scant. Further, to the best of our knowledge, the moderating role of working conditions in the organization and training and development programs conducted in organizations is not examined.…”
Section: Literature Review and Indian Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Extant research on WLB focused on the antecedent conditions (Alegre and Pasamar, 2018;Delanoeije et al, 2019;Gounder and Govender, 2018;Nizam and Kam, 2018), but the research focusing on the consequences of WLB is scant. Further, to the best of our knowledge, the moderating role of working conditions in the organization and training and development programs conducted in organizations is not examined.…”
Section: Literature Review and Indian Contextmentioning
confidence: 99%
“…The present study focuses on four important variables viz., job satisfaction, job commitment, job stress, work environment, and training and development. Extant research has studied the WLB concerning WFCs, FWCs, turnover, job satisfaction and job performance (Emslie and Hunt, 2009; Gounder and Govinder, 2018; Hon and Chan, 2013; Johari et al , 2018). Previous researchers did not consider the consequences of WLB except in one study by Johari et al (2018) who found that WLB is positively associated with job performance.…”
Section: Introductionmentioning
confidence: 99%